Fistula Laser Closure (FILAC)- Use of Radial Emitting Laser Probe - Islam, Md Tanvirul (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Abstract not available J Bangladesh Coll Phys Surg 2022; 40: 143-144